2020
DOI: 10.1097/ijg.0000000000001621
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intravenous Dexmedetomidine on Intraocular Pressure in Patients Undergoing Glaucoma Surgery Under Local Anesthesia: A Pilot Study

Abstract: Precis: Preoperative intravenous (IV) dexmedetomidine produced a 33% reduction in intraocular pressure (IOP) within 15 minutes of administration in patients with glaucoma. Purpose: To evaluate the effect of preoperative IV dexmedetomidine on IOP in adult patients undergoing glaucoma surgery under local anesthesia. Methods: In a prospective interventional case series, 12 patients with uncontrolled IOP (IOP>… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
0
0
Order By: Relevance
“…A recent pilot study showed dexmedetomidine produced significant IOP reduction (33%) in patients with glaucoma with reversal of effect at two hours. 47 However, its use as a LA adjunct in order to lower IOP has met with mixed reviews. 48,49 Our inclusion of dexmedetomidine in this commentary underscores its importance in changing our sedation regimen for many eye surgeries managed with an eye block and MAC.…”
Section: Dexmedetomidinementioning
confidence: 99%
“…A recent pilot study showed dexmedetomidine produced significant IOP reduction (33%) in patients with glaucoma with reversal of effect at two hours. 47 However, its use as a LA adjunct in order to lower IOP has met with mixed reviews. 48,49 Our inclusion of dexmedetomidine in this commentary underscores its importance in changing our sedation regimen for many eye surgeries managed with an eye block and MAC.…”
Section: Dexmedetomidinementioning
confidence: 99%